Gingival epithesis in periodontally compromised patient for esthetic solution - Filiz Keyf (Wolters Kluwer Medknow Publications, 2016)
Gingival recession caused due to periodontal disease disturbs patients because of sensitivity and esthetics. Gingival epithesis may be fixed or removable and can be made from silicones, acrylics, composite resins, or ceramics according to what is best suited for the case. The gingival epithesis is esthetically appealing and easy to maintain. This case report describes the fabrication and using of a gingival epithesis as a treatment modality to recreate the lost soft tissue esthetics.